Insect-mediated indirect interactions in tropical forest plant communities - Downey, H (2018)
A key aim in ecology is to understand the mechanisms that contribute to structuring diverse communities such as tropical forest plant communities. Much focus has been on the role of highly host-specific natural enemies. With data on the diet breadths of plant enemies accumulating, it is becoming increasingly clear that enemies are rarely strict specialists. It is therefore necessary to broaden investigations to non-specialist enemies contributing to structuring plant communities. In this thesis, I investigated the role of non-specialist insect enemies of seeds and seedlings in structuring plant communities in a forest in Panama, using a series of field investigations. Firstly, I used a quantitative food web approach to investigate the potential for indirect interactions between plant species in the Lauraceae family via their internally-feeding seed predators. I found high potential for enemy-mediated indirect interactions between species in this study system. These interactions are likely asymmetric and driven by the volume of fruit produced by each species. Secondly, using the same study system, I investigated patterns of seed predator attack across space and in response to the presence of conspecifics and alternative host species in the neighbourhood. I found that local and neighbourhood resource densities affected rates of insect attack and premature fruit abscission. Finally, using seedlings of Cordia trees and their associated insect herbivore I investigated the role of shared enemies at a later life stage. I detected negative conspecific density dependence as well as the potential for indirect interactions between plant species mediated by the shared herbivore. Overall, I show that insects caused significant amounts of damage to early life stages of plants, and that they have the potential to link the regeneration dynamics of their host species via enemy-mediated indirect interactions. This work contributes to a better understanding of the factors influencing the reproduction and recruitment of plant species in tropical forests.